Plutarch's political councils for good governance - Olano García, Hernán Alejandro (DIXI, 2019)
The present article of reflection on the Greek world and its present impact, part of a series on the application of the councils for good governance and is part of the research project “History of the Institutions-i”. It explores the writing of Plutarco de Queronea Moralia political councils, elaborated two thousand years ago, at the beginning of the 2nd century. It makes a reflection on the general political situation of the Greeks under Roman rule, in what is called “Hellenistic” or “Romanized Greek culture”. The text uses the historical examples used by Plutarch and, finally, includes a selection of recommendations that are still very topical today.
Keywords: good government; Greece; Greek intellectuals; Rome-Hellenism